The peak in performance across different abilities across age groups on the Wechsler Abbreviated Scales of Intelligence – second edition - Athanasou, James Anthony (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper describes the pattern of median performance on the sub-tests of the Wechsler Abbreviated Scales of Intelligence 2nd edition across age groups 6-90 years from the test standardisation (N=2300). The median raw-score for: (a) block design peaks at age 25; (b) matrix reasoning sub-test rises steeply up to ages 20-25; (c) vocabulary peaks at age 30-55; and (d) similarities task peaks in the age groups 30-45. When compared to performance at age 25, the major finding is that the decline at age 85 is highest for the block design (0.46 of age 25) then the matrix reasoning (0.52 of age 25) followed by similarities (0.78 of age 25) and finally, vocabulary (0.89 of age 25). There is continuing evidence for the differential decline in abilities. It applies particularly in the area of fluid intelligence and is consistent with previous findings in psychological assessment of cognitive abilities.